2023
DOI: 10.1108/meq-11-2022-0309
|View full text |Cite
|
Sign up to set email alerts
|

An extended TPB model of waste-sorting intention: a case study of Indonesia

Abstract: PurposeThis research investigates factors affecting the intention to sort waste. Specifically, this research aims to develop a waste-sorting intention model by extending the theory of planned behavior (TPB) model and to test the model to ensure the model's goodness-of-fit, validity and reliability.Design/methodology/approachThis research used a quantitative research methodology. Data were collected from 460 respondents using an online questionnaire. Some statistical analyses were performed to analyze the data:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Numerous research studies in the literature relating to waste have revealed that subjective norms have had an impact on waste minimization intentions [51,53,77]. Additionally, Rakhmawati et al [78] discovered that social norms significantly influenced visitor waste reduction. However, a study by So et al [79] found that intentions to reduce plastic trash in Hong Kong were unaffected by subjective standards.…”
Section: Subjective Norms and Local Tourists' Behavioral Intentions T...mentioning
confidence: 99%
“…Numerous research studies in the literature relating to waste have revealed that subjective norms have had an impact on waste minimization intentions [51,53,77]. Additionally, Rakhmawati et al [78] discovered that social norms significantly influenced visitor waste reduction. However, a study by So et al [79] found that intentions to reduce plastic trash in Hong Kong were unaffected by subjective standards.…”
Section: Subjective Norms and Local Tourists' Behavioral Intentions T...mentioning
confidence: 99%
“…In the same context, most of the studies that investigated intentions and behavior to reduce waste used an extended version of the TPB model instead of the original version. For instance, TPB has been extended to investigate the intentions to reduce food waste [ 47 , 48 , 49 , 50 ], plastic waste [ 51 ], waste-sorting [ 45 , 52 , 53 , 54 ], and energy consumption [ 55 ]. In addition, Aruta [ 56 ] used the extended TPB to explore intentions to reduce plastic use as one of the plastic waste reduction practices.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…[ 54 , 64 ] found that subjective norm has a significant effect on waste separation intention. In Taiwan, Fang et al [ 53 ] also found that social norms have a significant effect on waste reduction among visitors. Nevertheless, a study by So et al [ 51 ] showed that subjective norms had a non-significant influence in Hong Kong on plastic waste reduction intentions.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…(Kamalanon et al, 2022). Intense SN over behavior and strict control over will increase the actions taken, particularly when the friends, families, or relatives approve of an action, and might impact intention and behavior (Rakhmawati, Damayanti, Jati, & Astrini, 2023). The norm approach is more effective in establishing and fostering positive behavior in a collectivist culture like in Indonesia (Rahmafitria, Suryadi, Oktadiana, Putro, & Rosyidie, 2021).…”
Section: Subjective Norm (Sn)mentioning
confidence: 99%